Learning management through mobile apps - a new buzzword. (2017) - Mittal, Niti; Chaudhary, Monica; Alavi, Shirin
The innovation in mobile apps has forced educators to look for their suitability in providing learning. The various apps available for different platforms have something unique to offer in terms of user experience and functions. This paper examines the specific parameters which these apps have to offer the academia and organisations in terms of their use in educational setting. Web 2.0 technologies, particularly various mobile apps are changing the environment and possibilities for education. With the rapid development of these mobile apps users can now actively participate and construct their own learning experiences. Technologies like blogs, wikis, media sharing services and collaborative editing tools, promote collaboration and the sharing of knowledge by students and teachers. This research paper aims to explore the parameters associated with these mobile apps and analyse the performance of these five mobile apps to identify lessons for designing the most effective mobile apps by calculating their mobile application score (MAS).